Znaczenie dla Polski koncepcji informatora w dobrej wierze - Król, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The main purpose of this article is to show necessity to introduce a new method of protection against the corruption. This solution is very popular especially in countries with common law system. Poland seeks to reduce the corruption level but Transparency International’s report proved that all endeavors are not enough. This situation could be changed by whistleblowers. The article presents a social image of whistleblowers, their psychical condition after blowing the whistle and regulations which are necessary to protect them. This method will be effective in Poland if the government decides to introduce a statute which defines their position in a legal system.
Keywords: informator w dobrej wierze; korupcja zapobieganie